Sessão reflexiva como prática de formação continuada em serviço - Vieira, Iandra Cristina (2021)
Continuous education, which is centered at schools, poses a challenge. This essay is about the reflexive session which is a formative strategy. Through this formative practice, we aim to collaborate with the formation of critical professionals, who reflect on their practices and the learning of their students. To carry out this research, we started from the guiding question: What are the meanings that educational coordinators and teachers attribute to the reflective session as a space for continuous education in service?, with the general objective of analyzing the meanings that pedagogical-educational coordinators and teachers attribute to the reflective sessions as one of the spaces of continuous formation in service and with specific objectives: Know the meanings attributed to the reflexive session by teachers and pedagogical-educational coordinators; Identify if the meanings attributed to the reflexive session by the pedagogicaleducational coordination converge or diverge from the ones attributed by teachers; Identify the formative needs of the pedagogical-educational coordinator to work with the reflective sessions with the teachers, as one of the moments of continuous formation in service; Verify if, through reflective sessions, the formative needs of teachers are fulfilled; Present notes related to the reflective session as a practice of continuous formation in service, which can contribute to the expansion of reflection on the theme in the Education Network where these reflective sessions take place. The investigation is part of the qualitative research paradigm, having as a procedure for gathering information, a questionnaire carried out with teachers and two discussion groups, inspired by the concept of focal group approached by Gatti (2012), with pedagogicaleducational coordinators. The method of data analysis followed the assumptions of Prose Analysis (ANDRÉ, 1983). The context was composed by a network of private confessional schools, operating for over 100 years in Brazil. The participants are thirteen pedagogicaleducational coordinators who work in different segments, from nursery to high school, and 37 teachers who work in three schools that are members of this private education network, two located in São Paulo - the capital and the other one in a city in the countryside of the state. For the choice of theoretical references, which deal with teacher training, we indicate: Marcelo García (1999), Freire (1993, 2019), Nóvoa (1992, 1995, 2017) and Imbernón (2009, 2010, 2011); We deepened our understanding of these concepts and broadened our reflection for formation centered on the school and continuous formation in service, from Canary (1998, 2000), Placco (2010), Placco e Souza (2006, 2015), Almeida (2012, 2017), among others. As a reference for reflective practice we rely on Zeichner (1993, 2008) and the concept of Reflective Session, from the perspective of Magalhães (2004, 2007) and Liberali (2009, 2012).The data produced were organized around four axes, considering the themes and topics that emerged from the categorization: Concepts of training; Importance of reflective sessions; Training needs of coordinators and teachers; Contributions of the reflective session to training and professional practice. The results obtained indicate that reflexive session is considered, by coordinators and teachers, a formative practice of great relevance to professional, personal and collective development. The reflective session is felt by them as a formative practice that collaborates with professional development and reverberates with the students' learning process